Applying cognitive approach to teaching prepositions in business English: a case study - Zora Trninić (Anali Ekonomskog fakulteta u Subotici, 2023)
The paper sets out to investigate the potential advantages of applying insights from the field of cognitive linguistics to teaching prepositions in Business English over an approach relying on the traditional linguistic framework. For the study, three of the English prepositions were chosen: to, for, and at. Study participants were divided into two groups: an experimental group, which received a cognitive treatment of the three prepositions; and a control group, which received an instruction relying on traditional accounts. The participants were administered three tests in total: a pretest, an immediate posttest, and a delayed posttest. Their scores were taken on all three tests and then compared within each group and between the groups. To calculate the results, descriptive statistics, t-test of independent means and one-way ANCOVA were used. Grounding the expected results in expert literature, it was anticipated to obtain the results indicative of the advantage of the cognitive approach. According to the study results, the experimental group outperformed the control group at all levels of statistical analysis. The results suggest that a strategic incorporation of a cognitive view of the structure of language into the foreign language classroom could facilitate better understanding, more effective learning and long-term retention of the language points taught.     Keywords: applied cognitive linguistics, prepositions, business English, semantic network, conceptual metaphor. JEL classification: A20, A22, Z13